Simultaneous Intercalation of 1-Naphthylacetic Acid and Indole-3-butyric Acid into Layered Double Hydroxides and Controlled Release Properties. (18th May 2014) - Li, Shifeng; Shen, Yanming; Xiao, Min; Liu, Dongbin; Fan, Lihui; Zhang, Zhigang
Abstract : Controlled release formulations have been shown to have potential in overcoming the drawbacks of conventional plant growth regulators formulations. A controlled-release formulation of 1-naphthylacetic acid (NAA) and indole-3-butyric acid (IBA) simultaneous intercalated MgAl-layered double hydroxides (LDHs) was prepared. The synthetic nanohybrid material was characterized by various techniques, and release kinetics was studied. NAA and IBA anions located in the gallery of MgAl-LDHs with bilayer arrangement, and the nanohybrids particles were of typical plate-like shape with the lateral size of 50–100 nm. The results revealed that NAA and IBA have been intercalated into the interlayer spaces of MgAl-LDHs. The release of NAA and IBA fits pseudo-second-order model and is dependent on temperature, pH value, and release medium. The nanohybrids of NAA and IBA simultaneously intercalated in LDHs possessed good controlled release properties.